Teaching Microbiology by Celebrating Traditional Foods and Cultures from Morocco and Perú - Johana Meléndez (American Society for Microbiology, 2019)
According to a report published by the Center for Community College Student Engagement and others, global learning is considered one of the high-impact practices used to increase student engagement and motivation to learn. Engagement and motivation have also been linked to increased learning gains and improvement in the overall learning experience. Furthermore, global learning helps students explore other people’s cultures and worldviews, which is an important skill for students to gain in order to compete and adapt to solve the problems of our global society. Here, I discuss two class activities that faculty can adopt to implement global learning in their courses, with the purpose of engaging and motivating students to learn microbiology while celebrating some traditions from Morocco and Perú. Students researched traditional fermented foods and drinks from Perú and Morocco. Then, they answered guided questions to help them link the food items to microbiological concepts learned in class. For example: normal flora and fermentation were learned as students researched the process of making a Peruvian drink called “chicha de jora,” which is made from chewed corn that becomes fermented as it mixes with oral bacteria from saliva. While engaging in global learning, students learned some microbiology concepts; they passed the knowledge on to the campus community with poster presentations held during International Education Week. Based on students’ feedback and participation, I can conclude that teaching microbiology using global learning was engaging, promoted student learning, and motivated students to learn.